State-of-the-art in the documentation of the Papuan languages of Timor, Alor, Pantar, and Kisar; A bibliography - Schapper, Antoinette; Huber, Juliette (Wacana, Journal of the Humanities of Indonesia, 2012)
The Timor-Alor-Pantar (TAP) language family has a special place in South-East Asian linguistics; its members make up the western extreme of the Papuan language sphere. Along with an exhaustive bibliography of works on the TAP languages, this paper presents a state-of-the-art review of the ongoing documentation of the TAP language family in terms of both linguistic description and (pre-)historical reconstruction. The paper concludes with a consideration of the prospects for future studies of the TAP languages.